Rational Design of Suprastat: A Novel Selective Histone Deacetylase 6 Inhibitor with the Ability to Potentiate Immunotherapy in Melanoma Models - Noonepalle, Satish; Shen, Sida; Ptáček, Jakub; Tavares, Maurício T; Zhang, Guiping; Stránský, Jan; Pavlíček, Jiří; Ferreira, Glaucio M; Hadley, Melissa; Pelaez, Guido; Bařinka, Cyril; Kozikowski, Alan P; et al. (Journal of medicinal chemistry, 2020)
Selective inhibition of histone deacetylase 6 (HDAC6) is being recognized as a therapeutic approach for cancers. In this study, we designed a new HDAC6 inhibitor, named Suprastat, using in silico simulations. X-ray crystallography and molecular dynamics simulations provide strong evidence to support the notion that the aminomethyl and hydroxyl groups in the capping group of Suprastat establish significant hydrogen bond interactions, either direct or water-mediated, with residues D460, N530, and S531, which play a vital role in regulating the deacetylase function of the enzyme and which are absent in other isoforms. In vitro characterization of Suprastat demonstrates subnanomolar HDAC6 inhibitory potency and a hundred- to a thousand-fold HDAC6 selectivity over the other HDAC isoforms. In vivo studies reveal that a combination of Suprastat and anti-PD1 immunotherapy enhances antitumor immune response, mediated by a decrease of protumoral M2 macrophages and increased infiltration of antitumor CD8+ effector and memory T-cells.
Keywords: Animals; Molecular Dynamics Simulation; Rats; vodíková vazba; Female; Cell Line, Tumor; ženské pohlaví; inhibitory histondeacetylas; Histone Deacetylase 6; vazba proteinů; imunologické faktory; Immunotherapy; lidé; simulace molekulární dynamiky; Hydroxamic Acids; krystalografie rentgenová; jaterní mikrozomy; fenylmočovinové sloučeniny; Histone Deacetylase Inhibitors; kyseliny hydroxamové; Immunologic Factors; melanom; imunoterapie; racionální návrh léčiv; Melanoma; Microsomes, Liver; Hydrogen Bonding; krysa rodu Rattus; Drug Design; zvířata; Crystallography, X-Ray; Mice, Inbred C57BL; Phenylurea Compounds; Protein Binding; histondeacetylasa 6; nádorové buněčné linie; myši inbrední C57BL; Humans